Preparation method of nitrogen-sulfur-doped carbon-coated lithium iron phosphate

By using zein as a multifunctional source in lithium iron phosphate materials, and by ball milling and high-temperature treatment, nitrogen and sulfur-doped carbon-coated lithium iron phosphate was prepared, which solved the problem of uneven carbon coating during the material preparation process, significantly improving the electrochemical performance and industrial production adaptability of the material.

CN119898741APending Publication Date: 2025-04-29GUANGXI UNIV FOR NATITIES +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411971522.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, heteroatom-doped carbon-coated lithium iron phosphate materials are prone to cause uneven carbon coating during the preparation process, which in turn affects the performance of the material.

Method used

By putting iron phosphate and lithium carbonate together with zein as carbon sources, nitrogen and sulfur sources into a ball mill to form a precursor, and then high-temperature treatment in an atmosphere furnace, nitrogen and sulfur doped carbon-coated lithium iron phosphate was prepared.

Benefits of technology

This method simplifies the preparation process, improves the initial discharge specific capacity and rate performance of the material, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898741A_ABST
    Figure CN119898741A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a preparation method of nitrogen-sulfur-doped carbon-coated lithium iron phosphate, which comprises the following steps: mixing and ball-milling zein, ferric phosphate and lithium carbonate in different weight percentages under the action of a ball mill to obtain a precursor; and putting the precursor into an atmosphere furnace filled with shielding gas, and carrying out high-temperature treatment at a certain temperature to obtain the nitrogen-sulfur-doped carbon-coated lithium iron phosphate. The nitrogen-sulfur-doped carbon-coated lithium iron phosphate positive electrode material has relatively high initial discharge specific capacity, relatively good rate capability and relatively large lithium ion diffusion coefficient. The doped and modified carbon layer greatly improves the electron transmission capability, greatly improves the rate capability of the battery and prolongs the cycle life of the battery. The method is simple in preparation process, short in preparation period, low in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing nitrogen-sulfur doped carbon-coated lithium iron phosphate. Background Art

[0002] As an important part of the battery, the positive electrode material of lithium-ion batteries accounts for half of the battery cost and has attracted much attention in recent years. Lithium iron phosphate (LiFePO4) with olivine structure has low cost, rich element reserves, flat voltage platform (3.4V for Li + / Li), moderate theoretical specific capacity (170mAh / g), and high thermal stability have attracted much attention. Despite these advantages, it still has some disadvantages, such as low conductivity and poor lithium ion transmission ability at the boundary between electrolyte and solid electrode, resulting in poor rate performance, which are the main obstacles to the further application of lithium iron phosphate materials.

[0003] To date, a lot of research has been carried out to improve the electrochemical properties of lithium iron phosphate. Such as cation doping, reducing the size and morphology of the material (such as (010) surface exposed crystals), or carbon coating. Among them, carbon coating is the most effective means to significantly improve the surface electronic conductivity and lithium ion transport of lithium iron phosphate, and the cost is the lowest. Even at high current density, the active material can exert its maximum potential. However, simple carbon coating provides limited conductivity and does not completely solve the problem of poor rate performance of lithium iron phosphate positive electrode materials, especially the specific capacity provided at high current density is still limited.

[0004] On this basis, the introduction of heteroatoms (including N, S, B, P, F, etc.) into the carbon coating is a novel method for modifying carbon materials, which can further improve the electrochemical activity. Heteroatoms can act as electron donors, enhance the electron transport of carbon, destroy the ordered structure of graphite, and produce a large number of defects to promote the transport of lithium ions in the carbon layer. At present, there are two main methods for preparing heteroatom-doped carbon-coated lithium iron phosphate. First, the carbon-coated material is synthesized first, and then the heteroatoms to be incorporated are introduced. This process generally requires secondary calcination. This method increases the production cycle and cost. Second, in the process of preparing heteroatom-doped carbon-coated lithium iron phosphate, two different raw materials must be added, one is a carbon source and the other is a heteroatom source. The addition of two different raw materials may cause the heteroatom-doped carbon coating to be uneven, resulting in a decrease in product performance. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing nitrogen-sulfur doped carbon-coated lithium iron phosphate, aiming to overcome the technical problem that the introduction of different doping elements through different raw materials will lead to uneven carbon coating doped with heteroatoms, thereby causing reduced product performance.

[0006] To achieve the above object, the present invention provides a method for preparing nitrogen-sulfur doped carbon coated lithium iron phosphate, comprising the following steps:

[0007] Step 1: Weighing iron phosphate and lithium carbonate according to a certain molar ratio, and adding a certain amount of zein as a carbon source, a nitrogen source and a sulfur source;

[0008] Step 2: Put all the materials in step 1 into a ball mill and grind them to obtain a precursor;

[0009] Step 3: placing the precursor into an atmosphere furnace, introducing a protective gas, and calcining at a certain temperature to obtain nitrogen-sulfur doped carbon-coated lithium iron phosphate.

[0010] Optionally, in step 1, the molar ratio of iron phosphate to lithium carbonate is 2:(1-1.08).

[0011] Optionally, the carbon source, nitrogen source and sulfur source are provided by zein, and the mass ratio thereof is 0.1-0.2 of the sum of the mass of iron phosphate and lithium carbonate.

[0012] Optionally, during the grinding process in step 2, the ball mill speed is 300-700 r / min and the grinding time is 2-6 h.

[0013] Optionally, the protective gas is argon or nitrogen.

[0014] Optionally, the calcination process in step 3 is to increase the temperature to 650-700° C. at a heating rate of 5° C. / min and then keep the temperature for 4-10 hours.

[0015] Optionally, the first discharge specific capacity of the nitrogen-sulfur doped carbon-coated lithium iron phosphate at a current density of 0.1C is greater than or equal to 155 mAh / g.

[0016] Optionally, the capacity retention rate of the nitrogen-sulfur doped carbon-coated lithium iron phosphate after 500 cycles at 1C is greater than or equal to 85%.

[0017] Optionally, the discharge specific capacity of the nitrogen-sulfur doped carbon-coated lithium iron phosphate at a high current density of 20C is greater than or equal to 82 mAh / g.

[0018] Optionally, the nitrogen-sulfur doped carbon-coated lithium iron phosphate has a discharge specific capacity greater than or equal to 155 mAh / g when the current density returns to 0.1C.

[0019] The present invention provides a method for preparing nitrogen-sulfur doped carbon-coated lithium iron phosphate, specifically, zein containing nitrogen and sulfur elements in different weight percentages at the same time is mixed with iron phosphate and lithium carbonate in a ball mill to obtain a precursor; then the precursor is placed in an atmosphere furnace and treated at a certain temperature under the protection of a protective gas to obtain the nitrogen-sulfur doped carbon-coated lithium iron phosphate. It has been verified that the carbon-coated lithium iron phosphate doped with heteroatoms exhibits a higher initial discharge capacity, with a discharge capacity of 155.97 mAh / g at 0.1C, and a better discharge capacity at high current density, still 96.86 mAh / g at 10C, and greatly improves its rate performance, with discharge capacities of 155.97, 150.12, 139.91, 120.41, 110.31, 96.86, 84.06 and 161.40 mAh / g at 0.1C, 0.5C, 1C, 3C, 5C, 10C, 20C and finally back to 0.1C, respectively. It is suitable for large-scale industrial production because of its simple preparation method that conforms to industrial production, short preparation cycle and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 It is a schematic flow chart of the steps of a method for preparing nitrogen-sulfur doped carbon-coated lithium iron phosphate of the present invention.

[0022] Figure 2 3 is the XRD diagram of the nitrogen-sulfur doped carbon-coated lithium iron phosphate prepared in Example 1 of the present invention.

[0023] Figure 3 This is a SEM image of the nitrogen-sulfur doped carbon-coated lithium iron phosphate prepared in Example 1 of the present invention.

[0024] Figure 4 This is an XPS graph of the nitrogen-sulfur doped carbon-coated lithium iron phosphate prepared in Example 1 of the present invention.

[0025] Figure 5 It is a charge and discharge curve diagram of the lithium ion battery using nitrogen-sulfur doped carbon-coated lithium iron phosphate as the positive electrode material prepared in Example 1 of the present invention at a current density of 0.1C (1C=170mAh / g).

[0026] Figure 6This is a cycle test graph of a lithium-ion battery using nitrogen-sulfur-doped carbon-coated lithium iron phosphate as a positive electrode material prepared in Example 1 of the present invention at a current density of 1C.

[0027] Figure 7 It is a graph of the discharge specific capacity at different rates of a lithium ion battery using nitrogen-sulfur doped carbon-coated lithium iron phosphate as the positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0029] See also Figure 1 The present invention provides a method for preparing nitrogen-sulfur doped carbon-coated lithium iron phosphate, comprising the following steps:

[0030] S1: iron phosphate and lithium carbonate are weighed according to a certain molar ratio, and a certain amount of zein is added as a carbon source, a nitrogen source and a sulfur source;

[0031] S2: Put all the materials in step S1 into a ball mill to grind to obtain a precursor;

[0032] S3: placing the precursor into an atmosphere furnace, introducing a protective gas, and calcining at a certain temperature to obtain nitrogen-sulfur doped carbon-coated lithium iron phosphate.

[0033] The molar ratio of iron phosphate to lithium carbonate in step 1 is 2:(1-1.08).

[0034] The carbon source, nitrogen source and sulfur source are provided by zein, and the mass ratio thereof is 0.1-0.2 of the sum of the mass of iron phosphate and lithium carbonate.

[0035] During the grinding process in step 2, the ball mill speed is 300-700 r / min and the grinding time is 2-6 h.

[0036] The protective gas is argon or nitrogen.

[0037] The calcination process in step 3 is to increase the temperature to 650-700°C at a heating rate of 5°C / min and then keep the temperature for 4-10h.

[0038] The following is a detailed description of the embodiments. Figures 2 to 7 :

[0039] Example 1

[0040] (1) 3.0164 g of iron phosphate, 0.7759 g of lithium carbonate and 0.568 g of zein were placed in a ball mill and the speed was set to 400 r / min. The ball mill was milled for 4 h to obtain a lithium iron phosphate precursor.

[0041] (2) The precursor obtained in step (1) was mixed and ground, and then placed in an atmosphere furnace, heated to 700°C at a rate of 5°C / min in an argon atmosphere, and then kept at this temperature for 10 hours, and cooled to room temperature to obtain nitrogen-sulfur doped carbon-coated lithium iron phosphate. The obtained nitrogen-sulfur doped carbon-coated lithium iron phosphate was subjected to X-ray diffraction analysis, and the results are shown in FIG. Figure 2 ,Depend on Figure 2 It can be seen that the obtained product is lithium iron phosphate (JCPDS#81-1173), and the obtained nitrogen-sulfur doped carbon-coated lithium iron phosphate is detected by scanning electron microscopy. The test results are as follows: Figure 3 As shown by Figure 3 It can be seen that the diameter of nitrogen-sulfur doped carbon coated lithium iron phosphate is distributed in the range of 20-70nm, is evenly dispersed, and is a rough irregular sphere. XPS is used to detect the heteroatoms in the sample carbon layer. The test results are as follows Figure 4 As shown, the sample carbon layer contains N and S elements, proving the successful introduction of impurity elements.

[0042] (3) A battery was assembled using the nitrogen-sulfur-doped carbon-coated lithium iron phosphate prepared in step (2) as the positive electrode, a lithium sheet as the negative electrode, and 1M LiPF6 (1:1:1 / V:V:V) (DMC:EC:EMC) as the electrolyte for performance testing. The test results are shown in Figure 5 , Figure 6 and Figure 7 ,Depend on Figure 5 It can be seen that the discharge potential platform of nitrogen-sulfur-doped carbon-coated lithium iron phosphate as the positive electrode material of lithium-ion batteries is 3.4V. At a current density of 0.1C, the first discharge capacity of the material is 155.97mAh / g. After 500 cycles at 1C, there is still a discharge capacity of 116.05mAh / g, and the capacity retention rate is 87.1%. Figure 7 It can be seen that the material has excellent rate performance. When discharged at a high current density of 20C, it can still maintain a discharge specific capacity of 84.06mAh / g. When the current density returns to 0.1C, it can still maintain a discharge specific capacity of 161.40mAh / g, and can still return to the level before the rate test.

[0043] Example 2

[0044] (1) 3.0164 g of iron phosphate, 0.7759 g of lithium carbonate and 0.379 g of zein were placed in a ball mill and the speed was set to 400 r / min. The ball milling was performed for 4 h to obtain a lithium iron phosphate precursor;

[0045] (2) The precursors obtained in step (1) are mixed and ground and then placed in an atmosphere furnace. The temperature is raised to 700° C. at a rate of 5° C. / min in an argon atmosphere, and then kept at this temperature for 10 h. The mixture is cooled to room temperature to obtain nitrogen-sulfur-doped carbon-coated lithium iron phosphate.

[0046] (3) The nitrogen-sulfur-doped carbon-coated lithium iron phosphate prepared in step (2) was used as the positive electrode, the lithium sheet was used as the negative electrode, and 1M LiPF6 (1:1:1 / V:V:V) (DMC:EC:EMC) was used as the electrolyte to assemble a battery for performance testing. When the nitrogen-sulfur-doped carbon-coated lithium iron phosphate was used as the positive electrode material of the lithium-ion battery, its discharge potential platform was about 3.4V. At a current density of 0.1C, the material had an initial discharge capacity of 137.78mAh / g, and after 500 cycles at 1C, it still had a discharge capacity of 96.87mAh / g, and a capacity retention rate of 81.2%. The rate performance test showed that the material had excellent rate performance, and could still maintain a discharge capacity of 82.36mAh / g when discharged at a high current density of 20C. When the current density returned to 0.1C, it could still maintain a discharge capacity of 141.72mAh / g, and could still return to the level before the rate test.

[0047] Example 3

[0048] (1) 3.0164 g of iron phosphate, 0.7759 g of lithium carbonate and 0.758 g of zein were placed in a ball mill and the speed was set to 400 r / min. The ball mill was milled for 4 h to obtain a lithium iron phosphate precursor;

[0049] (2) The precursors obtained in step (1) are mixed and ground and then placed in an atmosphere furnace. The temperature is raised to 700° C. at a rate of 5° C. / min in an argon atmosphere, and then kept at this temperature for 10 h. The mixture is cooled to room temperature to obtain nitrogen-sulfur-doped carbon-coated lithium iron phosphate.

[0050] (3) The nitrogen-sulfur-doped carbon-coated lithium iron phosphate prepared in step (2) was used as the positive electrode, the lithium sheet was used as the negative electrode, and 1M LiPF6 (1:1:1 / V:V:V) (DMC:EC:EMC) was used as the electrolyte to assemble a battery for performance testing. When the nitrogen-sulfur-doped carbon-coated lithium iron phosphate was used as the positive electrode material of the lithium-ion battery, its discharge potential platform was about 3.4V. At a current density of 0.1C, the first discharge specific capacity of the material was 131.33mAh / g. After 500 cycles at 1C, there was still a discharge specific capacity of 59.41mAh / g, and the capacity retention rate was 80.4%. It can be seen from the rate performance test that the material has excellent rate performance. When discharged at a high current density of 20C, it can still maintain a discharge specific capacity of 75.27mAh / g. When the current density returns to 0.1C, it can still maintain a discharge specific capacity of 132.15mAh / g, and can still return to the level before the rate test.

[0051] Example 4

[0052] 3.0164 g of iron phosphate, 0.7906 g of lithium carbonate and 0.568 g of zein were placed in a ball mill, and the speed was set to 400 r / min, and ball milled for 4 h to obtain a lithium iron phosphate precursor;

[0053] The precursor obtained in step (1) is mixed and ground and then placed in an atmosphere furnace. The temperature is raised to 700° C. at a rate of 5° C. / min in an argon atmosphere, then kept at this temperature for 10 hours and cooled to room temperature to obtain nitrogen-sulfur-doped carbon-coated lithium iron phosphate.

[0054] The nitrogen-sulfur-doped carbon-coated lithium iron phosphate prepared in step (2) was used as the positive electrode, the lithium sheet was used as the negative electrode, and 1MLiPF6 (1:1:1 / V:V:V) (DMC:EC:EMC) was used as the electrolyte to assemble a battery for performance testing. The test results show that the nitrogen-sulfur-doped carbon-coated lithium iron phosphate is used as the positive electrode material of the lithium ion battery, and its discharge potential platform is about 3.4V. At a current density of 0.1C, the material has an initial discharge capacity of 152.84mAh / g, and after 500 cycles at 1C, there is still a discharge capacity of 112.58mAh / g, and the capacity retention rate is 82.9%. From the rate performance test, it can be seen that the material has excellent rate performance, and can still maintain a discharge capacity of 78.32mAh / g when discharged at a high current density of 20C, and can still maintain a discharge capacity of 153.62mAh / g when the current density returns to 0.1C, and can still return to the level before the rate test.

[0055] Example 5

[0056] (1) 3.0164 g of iron phosphate, 0.7759 g of lithium carbonate and 0.568 g of zein were placed in a ball mill and the speed was set to 600 r / min. The ball mill was milled for 4 h to obtain a lithium iron phosphate precursor;

[0057] (2) The precursors obtained in step (1) are mixed and ground and then placed in an atmosphere furnace. The temperature is raised to 700° C. at a rate of 5° C. / min in an argon atmosphere, and then kept at this temperature for 10 h. The mixture is cooled to room temperature to obtain nitrogen-sulfur-doped carbon-coated lithium iron phosphate.

[0058] (3) The nitrogen-sulfur-doped carbon-coated lithium iron phosphate prepared in step (2) was used as the positive electrode, the lithium sheet was used as the negative electrode, and 1M LiPF6 (1:1:1 / V:V:V) (DMC:EC:EMC) was used as the electrolyte to assemble a battery for performance testing. The test results show that the nitrogen-sulfur-doped carbon-coated lithium iron phosphate is used as the positive electrode material of the lithium ion battery, and its discharge potential platform is about 3.4V. At a current density of 0.1C, the material has an initial discharge capacity of 154.52mAh / g, and after 500 cycles at 1C, it still has a discharge capacity of 115.24mAh / g, and a capacity retention rate of 84.3%. The rate performance test shows that the material has excellent rate performance. When discharged at a high current density of 20C, it can still maintain a discharge capacity of 76.29mAh / g. When the current density returns to 0.1C, it can still maintain a discharge capacity of 155.16mAh / g, and can still return to the level before the rate test.

[0059] Example 6

[0060] (1) 3.0164 g of iron phosphate, 0.7759 g of lithium carbonate and 0.568 g of zein were placed in a ball mill and the speed was set to 400 r / min. The ball mill was milled for 6 h to obtain a lithium iron phosphate precursor;

[0061] (2) The precursors obtained in step (1) are mixed and ground and then placed in an atmosphere furnace. The temperature is raised to 700° C. at a rate of 5° C. / min in an argon atmosphere, and then kept at this temperature for 10 h. The mixture is cooled to room temperature to obtain nitrogen-sulfur-doped carbon-coated lithium iron phosphate.

[0062] (3) The nitrogen-sulfur-doped carbon-coated lithium iron phosphate prepared in step (2) was used as the positive electrode, the lithium sheet was used as the negative electrode, and 1M LiPF6 (1:1:1 / V:V:V) (DMC:EC:EMC) was used as the electrolyte to assemble a battery for performance testing. The test results show that the nitrogen-sulfur-doped carbon-coated lithium iron phosphate is used as the positive electrode material of the lithium ion battery, and its discharge potential platform is about 3.4V. At a current density of 0.1C, the material has an initial discharge capacity of 145.68mAh / g, and after 500 cycles at 1C, it still has a discharge capacity of 107.41mAh / g, and a capacity retention rate of 79.52%. The rate performance test shows that the material has excellent rate performance. When discharged at a high current density of 20C, it can still maintain a discharge capacity of 72.93mAh / g. When the current density returns to 0.1C, it can still maintain a discharge capacity of 144.38mAh / g, and can still return to the level before the rate test.

[0063] Example 7

[0064] (1) 3.0164 g of iron phosphate, 0.7759 g of lithium carbonate and 0.568 g of zein were placed in a ball mill and the speed was set to 400 r / min. The ball mill was milled for 4 h to obtain a lithium iron phosphate precursor;

[0065] (2) The precursors obtained in step (1) are mixed and ground and then placed in an atmosphere furnace. The temperature is raised to 650° C. at a rate of 5° C. / min in an argon atmosphere, then kept at this temperature for 10 h, and cooled to room temperature to obtain nitrogen-sulfur-doped carbon-coated lithium iron phosphate.

[0066] (3) The nitrogen-sulfur-doped carbon-coated lithium iron phosphate prepared in step (2) was used as the positive electrode, the lithium sheet was used as the negative electrode, and 1M LiPF6 (1:1:1 / V:V:V) (DMC:EC:EMC) was used as the electrolyte to assemble a battery for performance testing. The test results show that the nitrogen-sulfur-doped carbon-coated lithium iron phosphate is used as the positive electrode material of the lithium ion battery, and its discharge potential platform is about 3.4V. At a current density of 0.1C, the material has an initial discharge capacity of 141.43mAh / g, and after 500 cycles at 1C, it still has a discharge capacity of 110.35mAh / g, and a capacity retention rate of 82.4%. The rate performance test shows that the material has excellent rate performance. When discharged at a high current density of 20C, it can still maintain a discharge capacity of 79.63mAh / g. When the current density returns to 0.1C, it can still maintain a discharge capacity of 140.72mAh / g, and can still return to the level before the rate test.

[0067] Example 8

[0068] (1) 3.0164 g of iron phosphate, 0.7759 g of lithium carbonate and 0.568 g of zein were placed in a ball mill and the speed was set to 400 r / min. The ball mill was milled for 4 h to obtain a lithium iron phosphate precursor;

[0069] (2) The precursor obtained in step (1) is mixed and ground and then placed in an atmosphere furnace. The temperature is raised to 700° C. at a rate of 5° C. / min in an argon atmosphere, then kept at this temperature for 6 hours, and cooled to room temperature to obtain nitrogen-sulfur-doped carbon-coated lithium iron phosphate.

[0070] (3) The nitrogen-sulfur-doped carbon-coated lithium iron phosphate prepared in step (2) was used as the positive electrode, the lithium sheet was used as the negative electrode, and 1M LiPF6 (1:1:1 / V:V:V) (DMC:EC:EMC) was used as the electrolyte to assemble a battery for performance testing. The test results show that the nitrogen-sulfur-doped carbon-coated lithium iron phosphate is used as the positive electrode material of the lithium ion battery, and its discharge potential platform is about 3.4V. At a current density of 0.1C, the first discharge specific capacity of the material is 135.42mAh / g, and after 500 cycles at 1C, there is still a discharge specific capacity of 98.56mAh / g, and the capacity retention rate is 81.61%. From the rate performance test, it can be seen that the material has excellent rate performance. When discharged at a high current density of 20C, it can still maintain a discharge specific capacity of 73.68mAh / g. When the current density returns to 0.1C, it can still maintain a discharge specific capacity of 136.29mAh / g, and can still return to the level before the rate test.

[0071] Example 9

[0072] 3.0164 g of iron phosphate, 0.7759 g of lithium carbonate and 0.568 g of zein were placed in a ball mill, and the speed was set to 400 r / min, and ball milled for 4 h to obtain a lithium iron phosphate precursor;

[0073] The precursor obtained in step (1) is mixed and ground and then placed in an atmosphere furnace. The temperature is raised to 700° C. at a rate of 5° C. / min in a nitrogen atmosphere, then kept at this temperature for 10 hours and cooled to room temperature to obtain nitrogen-sulfur doped carbon-coated lithium iron phosphate.

[0074] The nitrogen-sulfur-doped carbon-coated lithium iron phosphate prepared in step (2) was used as the positive electrode, the lithium sheet was used as the negative electrode, and 1MLiPF6 (1:1:1 / V:V:V) (DMC:EC:EMC) was used as the electrolyte to assemble a battery for performance testing. The test results show that the nitrogen-sulfur-doped carbon-coated lithium iron phosphate is used as the positive electrode material of the lithium ion battery, and its discharge potential platform is about 3.4V. At a current density of 0.1C, the first discharge specific capacity of the material is 153.57.68mAh / g, and after 500 cycles at 1C, there is still a discharge specific capacity of 114.27mAh / g, and the capacity retention rate is 85.61%. From the rate performance test, it can be seen that the material has excellent rate performance. When discharged at a high current density of 20C, the discharge specific capacity can still be maintained at 78.64mAh / g. When the current density returns to 0.1C, the discharge specific capacity can still be maintained at 155.36mAh / g, and the discharge specific capacity can still be returned to the level before the rate test.

[0075] Comparative Example 1

[0076] Conventional heteroatom-doped lithium iron phosphate is used as the positive electrode material of lithium-ion batteries. Its discharge potential platform is about 3.4V. At a current density of 0.1C, the material has an initial discharge capacity of 140.5mAh / g. After 500 cycles at 1C, it still has a discharge capacity of 88.4mAh / g, and a capacity retention rate of 62.9%. The rate performance test shows that the material has poor rate performance. When discharged at a high current density of 20C, it can only maintain a discharge capacity of 53.2mAh / g. When the current density returns to 0.1C, it can only maintain a discharge capacity of 121.5mAh / g, and has not returned to the level before the rate test.

[0077] What is disclosed above is only one or more preferred embodiments of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and making equivalent changes according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing nitrogen-sulfur doped carbon-coated lithium iron phosphate, characterized in that: The following steps are involved: Step 1: Weighing iron phosphate and lithium carbonate according to a certain molar ratio, and adding a certain amount of zein as a carbon source, a nitrogen source and a sulfur source; Step 2: Put all the materials in step 1 into a ball mill and grind them to obtain a precursor; Step 3: placing the precursor into an atmosphere furnace, introducing a protective gas, and calcining at a certain temperature to obtain nitrogen-sulfur doped carbon-coated lithium iron phosphate.

2. The method for preparing nitrogen-sulfur doped carbon-coated lithium iron phosphate according to claim 1, characterized in that: The molar ratio of iron phosphate to lithium carbonate in step 1 is 2:(1-1.08).

3. The method for preparing nitrogen-sulfur doped carbon coated lithium iron phosphate according to claim 1, characterized in that: The added amount of the zein is 0.1-0.2 of the sum of the mass of the iron phosphate and the lithium carbonate.

4. The method for preparing nitrogen-sulfur doped carbon coated lithium iron phosphate according to claim 1, characterized in that: During the grinding process in step 2, the ball mill speed is 300-700 r / min and the grinding time is 2-6 h.

5. The method for preparing nitrogen-sulfur doped carbon coated lithium iron phosphate according to claim 1, characterized in that: The protective gas is argon or nitrogen.

6. The method for preparing nitrogen-sulfur doped carbon coated lithium iron phosphate according to claim 1, characterized in that: The calcination process in step 3 is to increase the temperature to 650-700°C at a heating rate of 5°C / min and then keep the temperature for 4-10h.

7. The method for preparing nitrogen-sulfur doped carbon coated lithium iron phosphate according to claim 1, characterized in that: The first discharge specific capacity of the nitrogen-sulfur doped carbon-coated lithium iron phosphate at a current density of 0.1C is greater than or equal to 155 mAh / g.

8. The method for preparing nitrogen-sulfur doped carbon coated lithium iron phosphate according to claim 1, characterized in that: The capacity retention rate of the nitrogen-sulfur doped carbon coated lithium iron phosphate after 500 cycles at 1C is greater than or equal to 85%.

9. The method for preparing nitrogen-sulfur doped carbon coated lithium iron phosphate according to claim 1, characterized in that: The discharge specific capacity of the nitrogen-sulfur doped carbon-coated lithium iron phosphate at a high current density of 20C is greater than or equal to 82 mAh / g.

10. The method for preparing nitrogen-sulfur doped carbon-coated lithium iron phosphate according to claim 9, characterized in that: The nitrogen-sulfur doped carbon coated lithium iron phosphate has a discharge specific capacity greater than or equal to 155 mAh / g when the current density returns to 0.1C.